Taá¹wÄ«ru WasÄ«lah at-Taâ€˜lÄ«mu LimahÄrati al-QirÄâ€™ah â€˜Abru NizÄmi IdÄrati at-Taâ€˜allumi (LMS) Moodle FÄ« al-Madrasah aá¹¡-á¹ anÄwiyyah al-HukÅ«miyyah al-â€™Ula Situbondo: Development of Learning Media for Maharah Kalam Through LMS Moodle at Man 1 Situbondo - Ahmad Fajri Fadhili; Muhammad Syaiful Bahri Hidayat (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
Learning during the pandemic demands to be more creative and innovative. However, the problem at school is that teachers have not been able to realize optimal learning because there is no adequate media. In connection with this, the researchers intend to develop learning media. This study aims 1) to describe the development of learning media-based (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo, 2) to analyze the feasibility of developing learning media based (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo, 3) to measure the effectiveness of the use of media-based learning (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo.This study uses a research and development (R&D) approach. The development steps used in this research are research steps according to